Analisis Penerapan serta Hambatan Pemikiran Tokoh–Tokoh Ekonomi Klasik terhadap Sistem Ekonomi Masa Kini - Purba, Bonaraja; Sihombing, Anjel Ezania; Azizah, Lutfiah Nur; Purba, Adyanto Armando (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Classic figures such as Adam Smith, David Ricardo, Thomas Robert Malthus, John Stuart Mill, and Jean Baptiste Say have put forward the basic concepts of understanding economics in the last century and in today's economy. Its application to the economic system includes Family Planning Programs, Entrepreneurship ideas, and the existence of free markets in international trade. The goal of this application is to fill job vacancies, improve the efficiency of economic activities, and maintain economic stability. However, in the application of these classic economic concepts, there are still some obstacles, one of which is food crises. Therefore, this article aims to provide an understanding of how the application and obstacles of classic economic theory are applied to today's economic system, so that classic economic theory can be adapted to address the obstacles in today's economic system.